Radiological, vascular osteochondrosis occurs in the distal tarsus, and may cause osteoarthritis. (9th March 2021) - Sigurdsson, Sigurdur F.; Olstad, Kristin; Ley, Charles J.; Björnsdóttir, Sigriður; Griffiths, David J.; Fjordbakk, Cathrine T.
Abstract: Background: Osteochondrosis occurs due to failure of the blood supply to growth cartilage. Osteochondrosis lesions have been identified in small tarsal bones and suggested to cause distal tarsal osteoarthritis; however, it has not been determined whether distal tarsal osteochondrosis lesions were the result of vascular failure. Objectives: To perform post‐mortem arterial perfusion and micro‐computed tomography (CT) of the central (CTB) and third tarsal bones (TIII) of fetuses and foals up to 5 months old, to describe tarsal development and any lesions detected. Study design: Descriptive, nonconsecutive case series. Methods: Twenty‐three animals that died or were euthanased from 228 days of gestation to 5 months old were collected, comprising two fetuses and nine foals of miscellaneous breeds and 12 Icelandic Horse foals, a breed with high prevalence of distal tarsal osteoarthritis. One hindlimb from each foal was perfused arterially with barium, and the CTB and TIII were examined with micro‐CT. Results: Perfusion yielded partial information from 41% of the animals. The CTB and TIII were supplied by nutrient arteries and perichondrial vessels with vertical, transverse and circumferential configurations. Fourteen of the 23 (61%) animals had focal defects in the ossification front, that is, radiological osteochondrosis. The majority of lesions matched the configuration and development of vertical vessels. Additionally, full‐thickness, cylindrical defects matched transverse vessels, and the long axes of some dorsal lesions matched circumferential vessels. Main limitations: Lack of histological validation. Conclusions: Post‐mortem perfusion was poor for examination of the blood supply to the growth cartilage of the CTB and TIII. Radiological osteochondrosis lesions were compatible with vascular failure because they were focal, and because lesion geometry matched vessel configuration. The relationship between osteochondrosis and distal tarsal osteoarthritis warrants further investigation.